New roles in civil society : current and potential roles in decentralised decision-making in rural Nepal : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Sherpa, Helen Bernadette (Massey University, 2004)
This study attempts to develop a better understanding of the roles civil society plays in rural Nepal. Makawanpur district has a diverse population and villages both remote and close to national highways and urban centres. The study was carried out during a period of political instability and civil war during which the functioning democratic government was replaced by an administration appointed by the King. At the community level an active civil society undertakes a range of roles and responsibilities. The most significant organisations involving large numbers of people were those contributing directly to supporting livelihoods, including dairy cooperatives, savings and credit groups, forest and water user groups. State-controlled sectors such as education and health had weaker participation. Religious and ethnic organisations do not play significant roles while non-government organisations are present and contribute to welfare and development but do not have large memberships Many civil society organisations were "induced" but over time had evolved and developed their own agendas. Roles being undertaken included management of resources and utilities, supporting poverty alleviation and improved livelihoods, participation in decentralised governance and addressing social issues. Microfinance was a powerful motivating factor used both to form and keep groups together. Groups claimed "inclusiveness" but this could not be independently verified in this study. Civil society theory holds that a healthy society balances the Prince (State), Merchant (commercial sector) and Citizen (civil society). Applying and understanding this theory in a rural environment is challenging and raises many questions as to what "balance" would look like. The State presence is small, mostly in the form of schools and health posts, but it controls policies that affect civil society. Organisations felt they had little influence on policy. The commercial sector is also very poorly developed. In this environment, community based civil society organisations undertake many roles. Civil society is complex and can only be viewed in context of the given point in history and specific community power relations. As communities undertake more roles and responsibilities, they will need to be better understood and supported by the development industry if they are to achieve their full potential.
Keywords: Nepal; Rural development; Political aspects; Non-governmental organizations; Civil society; Politics and government -- 1990-